(untitled) (Research, Society and Development, 2021)
Milk production in the world is growing, as it represents part of the world economy. In view of this scenario, the concern with the quantity and quality of milk and the herd has been relevant. Heat stress is the consequence of the absence of shade on rural properties, impairing the production and reproduction of animals. In this regard, silvopastoral systems have been favorable for the performance of dairy cows, since shading promotes positive effects on milk production, well-being, comfort and fertility, in addition, increasing the availability of nutrients in the soil, improving pastures. Therefore, the aim of this review was to present the benefits of shading provided by silvopastoral systems in milk production and thermal comfort of animals.